The Role of the Creative Economy in Accelerating the Recovery of SMEs from the Impact of the Covid-19 Pandemic (Study on Table and Chair Crafts from Tires) - Gunartin Gunartin (Universitas Muhammadiyah Sorong, 2022)
This paper aims to describe the role of the creative economy in accelerating the recovery of SMEs due to the Covid-19 pandemic. The approach used is descriptive qualitative. Data were collected through observation, interviews and documentation. The Covid-19 pandemic has had an impact on various sectors which in the weakening of the national economy. To survive in business, you must be competitive and able to adapt to changes. Based on the results of the study, the creative economy of tables and chairs from recycling used tires was able to survive the Covid-19 pandemic and contribute to improving the community's economy. The creative economy is one solution to reduce unemployment, because the rate of population growth is not proportional to the rate of employment. The creative economy synergizes with SMEs to improve the competitiveness and quality of SMEs which have a major role in the economy both in the economic and social fields, namely creating jobs. Meanwhile, human resource development and easy access to capital financing can help accelerate the recovery of SMEs from the impact of the COVID-19 pandemic